Proceedings of the 51st Annual ACM SIGACT Symposium on Theory of Computing 2019
DOI: 10.1145/3313276.3316328
|View full text |Cite
|
Sign up to set email alerts
|

Planar point sets determine many pairwise crossing segments

Abstract: We show that any set of n points in general position in the plane determines n 1−o(1) pairwise crossing segments. The best previously known lower bound, Ω ( √ n), was proved more than 25 years ago by Aronov, Erdős, Goddard, Kleitman, Klugerman, Pach, and Schulman. Our proof is fully constructive, and extends to dense geometric graphs.Let V be a set of n points in general position in the plane, that is, assume that no 3 points of V are collinear. A geometric graph is a graph G = (V, E) whose vertex set is V and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…This corollary is also asymptotically best possible. To see this, for n > (k − 1) 2 > 0 and a sequence A = (a i ) n i=1 of distinct real numbers, we can apply Corollary 6.1 with = (64k) −1 to A and obtain an -monotone subsequence S and then apply Lemma 2.1 in [13] to S to conclude a blockmonotone subsequence of depth k and block-size Ω(n/k 2 ). So Corollary 6.1 implies Theorem 1.1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corollary is also asymptotically best possible. To see this, for n > (k − 1) 2 > 0 and a sequence A = (a i ) n i=1 of distinct real numbers, we can apply Corollary 6.1 with = (64k) −1 to A and obtain an -monotone subsequence S and then apply Lemma 2.1 in [13] to S to conclude a blockmonotone subsequence of depth k and block-size Ω(n/k 2 ). So Corollary 6.1 implies Theorem 1.1.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, let us remark that a recent result due to Pach, Rubin, and Tardos [13] shows that every n-element planar point set in general position determines at least n/e O( √ log n) pairwise crossing segments. By using Theorem 1.3 instead of Lemma 3.3 from their paper, one can improve the constant hidden in the O-notation.…”
Section: Applicationsmentioning
confidence: 96%
“…Given three pointsets in the plane, P, Q, and S, we say that the three sets are mutually avoiding set if no line determined by two points in a set intersects the two convex hulls of the other two pointsets. The concept of mutually avoiding sets are often used in discrete and computational geometry, like in [2], [40], [25] and [27]. It was proved in [2] that any planar n-element pointset in general position contains two mutually avoiding subsets of size at least n/12.…”
Section: Elekes' Conjecture For Collinear Triplesmentioning
confidence: 99%
“…Given n, perfect matching with exactly µ = n/2 2 crossings belongs to an active area of research around so-called crossing-family (see for example [8,9]). Only very recently it was shown that any set of n points in general position contains a crossing families (a perfect matching with µ crossings) of almost linear size, more precisely, of size n 1−o(1) [10]. This was the first substantial improvement after 25 years.…”
Section: Introductionmentioning
confidence: 99%